AI-GENERATED COMPOSITIONS IN MUSIC EDUCATION - Wani, Tanveer Ahmad; Sarna, Shilpi; Gupta, Shikhar; Rai, Supriya; Singh, Jaskirat; Arora, Neha; Chavan, Pranali (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the introduction of the creative process into the sphere of music learning, the introduction of the Artificial Intelligence (AI) has changed the way of composing, analyzing, and learning. The compositions created by AI give educators and learners new tools that could be applied to generate creativity and composing, and their interpretation of the musical form. The paper explains how AI has been used more and more as a potent application in the field of music education because it has evolved into a neural network-based network, such as AIVA, Amper Music, and MuseNet. The research question examined in the paper with the assistance of a mixed-methods research incorporating surveys, interviews, and classroom activities is how the AI-assisted tools impact the engagement, creativity, and compositional abilities of students. The findings indicate that AI-generated music can help to enhance the appreciation of the compositional processes and experimentation and collaboration. Nevertheless, the study also finds obstacles, such as the presence of ethical issues relating to authorship, the possible excessive dependence on technology, and the necessity to establish a balance between intuition and algorithms. Case studies demonstrate effective educational applications, focusing on the use of teacher facilitation and curriculum integration to make AI pedagogical potential the most effective way to utilize it.